Monetary theory - Rabin, Alan A. (Cheltenham, UK ; Northampton, MA : E. Elgar, 2004)
The book focus on the enduring fundamentals of monetary disequilibrium theory. it provides the theory of orthodox monetarism with special emphasis on the process involved which underlies the monetarist evidence.
Includes bibliographical references.
nmn 10/05/17
Loan
Keywords: Money; Monetary policy